Bifunctional covalent organic frameworks with two dimensional organocatalytic micropores - Shinde, Digambar Balaji; Kandambeth, Sharath; Pachfule, Pradip; Kumar, Raya Rahul; Banerjee, Rahul (Chemical Communications, 2015)
We report the successful incorporation of bifunctional (acid/base) catalytic sites in the crystalline organocatalytic porous COF (2,3-DhaTph). Due to the presence of acidic (catachol) and basic (porphyrin) sites, 2,3-DhaTph shows significant selectivity, reusability, and excellent ability to perform the cascade reaction.